Aprimoramento de um detector de espalhamento de luz laser em baixo ângulo e seu uso in-line na caracterização morfológica de misturas poliméricas bifásicas - Gasparini, Thiago Manha (Universidade Federal de São Carlos, 2019)
A new prototype of the optical detector based on low angle laser light scattering (LALLS) was developed in order to follow in-line the morphology of polymer blends and composites during processing. For this, light from a laser source is scattered by the sample, solid or not, and collected by the detector plate. The signals are amplified by electronic circuits, converted into digital data and sent to a computer, in which real-time analysis of the pattern and scattered light profile is performed. Thus, valuable information is provided to help elucidate the size and shape of the second phase present. The LALLS detector was tested on bench using standard films, including those of a polyethylene blend, which revealed that the degree of anisotropy is proportional to the draw ratio by an asymptotic relationship. The in-line characterization on the CSS450 controlled simple shear system used samples of a blend of polypropylene and polystyrene, revealing by means of the curves of transmitted light intensity and the degree of anisotropy, the comminution and deformation of the dispersed second phase particles. Finally, the device was tested in-line on extrusion of polystyrene with transient concentration of the dispersed phase of alumina or polypropylene. Unlike the alumina, the dispersed particles of PP have variable morphology and the curve of the degree of anisotropy indicated that the particles are elongated in the direction of the flow and that the deformation is slight affected by concentration. Based on the Mie scattering theory, three models were applied during extrusion to estimate the mean particle diameter. In this way, the LALLS detector device confirmed to be a practical tool that allows real-time characterization of polymer systems morphology during processing.
Improvement of a low angle light laser scattering detector and its use in-line on the morphological characterization of biphasic polymer blends
Keywords: Espalhamento de luz laser em baixo ângulo; Reo-óptica; Caracterização morfológica; Sistemas poliméricos bifásicos; Cisalhamento simples; Low angle laser light scattering; Rheo-optics; Morphological characterization; Biphasic polymer systems; Simple shear; Dispersión de luz láser en ángulo bajo; Caracterización morfológica; Cizallamiento simple; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA